2019
DOI: 10.1634/theoncologist.2018-0718
|View full text |Cite
|
Sign up to set email alerts
|

Recent Therapeutic Advances and Change in Treatment Paradigm of Patients with Merkel Cell Carcinoma

Abstract: Merkel cell carcinoma (MCC) is a rare, aggressive, primary cutaneous neuroendocrine tumor that typically presents as an indurated nodule on sun‐exposed areas of the head and neck in the white population. Major risk factors include immunosuppression, UV light exposure, and advanced age. Up to 80% of MCC are associated with Merkel cell polyomavirus. About 50% of patients present with localized disease, and surgical resection with or without adjuvant radiotherapy is generally indicated in this context. However, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 63 publications
(96 reference statements)
0
19
0
Order By: Relevance
“…Our findings support the role of immunotherapy in MCC-UP, which might include agents that block PD-1/PD-L1 axis and regulatory T-cell function or enhance T-cell activity. Several promising clinical trials of immune checkpoint inhibitors have demonstrated responses to anti-PD-L1 (avelumab, atezolizumab) and anti-PD1 (nivolumab, pembrolizumab) therapy [ 37 ]. In addition, a case of MCC-UP with a good response to avelumab has recently been reported [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support the role of immunotherapy in MCC-UP, which might include agents that block PD-1/PD-L1 axis and regulatory T-cell function or enhance T-cell activity. Several promising clinical trials of immune checkpoint inhibitors have demonstrated responses to anti-PD-L1 (avelumab, atezolizumab) and anti-PD1 (nivolumab, pembrolizumab) therapy [ 37 ]. In addition, a case of MCC-UP with a good response to avelumab has recently been reported [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapeutic regimens including platinum-based combinations, etoposide, topotecan, taxanes and anthracyclines were widely used until 2016, leading to response rates in the range of 30–75%, and to median PFS and OS of approximately 3 and 10 months, respectively, in the first-line setting [ 161 , 162 , 163 , 164 , 165 ]. The immunosuppressive effect of chemotherapy is currently regarded as a possible mechanism accounting for the early development of resistance following treatment with cytotoxic agents in the context of a highly immunogenic cancer [ 166 ].…”
Section: Merkel Cell Carcinomamentioning
confidence: 99%
“…As a rare disease, MCC management requires MTB discussions to clarify any aspect of this complex scenario with dedicated specialists. Future improvement of MCC therapy, such as immune therapy 22 and other tailored treatment, requires multi-institutional collaborative groups and randomized trials.…”
Section: Resultsmentioning
confidence: 99%